Optimizing Educational Leadership: Building Sustainable Education in the 5.0 Era - Muhammad Baiqun Isbahi; Muhammad Mujtaba Mitra Zuana (Anjasmoro: Islamic Interdisciplinary Journal, 2023)
The topic of leadership is of great significance as it pertains to the effective guidance and direction of an educational institution. Leaders possess the authority to mobilise and exert influence over the tasks that are incumbent upon their roles and obligations. The objective of this study is to provide a comprehensive portrayal of school principals in their role as leaders within educational institutions during the 5.0 era. Additionally, the study seeks to examine the integration of the EMASLIM-FM concept into the function of educational leadership during this era. Furthermore, the study wants to depict school principals as visionary leaders in the field of education during the 5.0 era. The present study adopts a qualitative research design, employing a library research methodology. The data were acquired by a comprehensive review of literary sources, including books, ebooks, scholarly journal articles, dissertations, and other relevant publications. The utilisation of comparative analysis for data analysis. The analytical findings indicate that under the EMASLIM-FM framework, the role of the school principle encompasses various tasks, including education, management, administration, supervision, leadership, innovation, motivation, and mediation. In the 5.0 era, effective leadership necessitates that school administrators possess visionary competencies in order to transform their schools into comprehensive educational establishments. The importance of creative leadership cannot be overstated, since it is imperative to recognise that vision serves as a guiding principle within the realm of leadership. The principal should consider incorporating the concept of tangibility and measurability into the framework of the leadership wheel. The crucial factor in attaining the targeted educational objectives is the implementation of tangible measures.